2014
DOI: 10.1177/0363546513517539
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tendon-Derived Stem Cell Sheet for the Promotion of Graft Healing in Anterior Cruciate Ligament Reconstruction

Abstract: The TDSC sheet could potentially be used for the promotion of graft healing in ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 27 publications
4
120
0
Order By: Relevance
“…Supplementation with CTGF enriched a CD146 + TSPC subpopulation (likely derived from a perivascular source) and stimulated proliferation and tenogenic differentiation . This was consistent with several studies showing efficient tenogenic differentiation in TSPCs in parallel with downregulation of osteo‐, chondro‐, and adipogenic gene expression . In vivo delivery of CTGF also resulted in recruitment of CD146 + cells and improved tendon healing .…”
Section: Tspc Culture and Differentiation: Growth Factors Small Molesupporting
confidence: 86%
“…Supplementation with CTGF enriched a CD146 + TSPC subpopulation (likely derived from a perivascular source) and stimulated proliferation and tenogenic differentiation . This was consistent with several studies showing efficient tenogenic differentiation in TSPCs in parallel with downregulation of osteo‐, chondro‐, and adipogenic gene expression . In vivo delivery of CTGF also resulted in recruitment of CD146 + cells and improved tendon healing .…”
Section: Tspc Culture and Differentiation: Growth Factors Small Molesupporting
confidence: 86%
“…The results demonstrated that the cells derived from the cell sheets incorporated within the bone tunnel site and grafted tendon and that healing of the bone-tendon junction and the grafted tendon was significantly enhanced. Similarly, to promote early graft healing following ACL reconstruction in a rat model, Lui et al (47) wrapped a tendon-derived stem cell (TDSC) sheet around the ACL graft. At weeks 2, 6 and 12 after reconstruction, the TDSC group showed a time-dependent increase in tunnel bone mineral density and bone volume/total volume at the epiphyseal region of the tibial tunnel.…”
Section: Tendon Stem Cell Sheets For Tendon Tissue Engineeringmentioning
confidence: 99%
“…151 Tendon-derived stem cell sheets stimulated with CTGF promoted improved anterior cruciate ligament graft healing and biomechanics in vivo in rats, including improved osteointegration. 152 Similarly, cell sheets with CTGF and ascorbic acid enhanced biomechanical and histology-based outcomes at 8 weeks in an in vivo rat patellar tendon repair model. Further studies introducing CTGF and/or BMP growth factors with cells and biocompatible matrices will be important for defining the next generation of therapies for flexor tendon repair.…”
Section: Biologic Treatmentsmentioning
confidence: 96%